Local Action with Global Impact: Highly Similar Infection Patterns of Human Viruses and Bacteriophages - Mariano, Rachelle (mSystems, 2016)
The investigation of host-pathogen interaction interfaces and their constituent factors is crucial for our understanding of an organism’s pathogenesis. Here, we explored the interactomes of HIV, hepatitis C virus, influenza A virus, human papillomavirus, herpes simplex virus, and vaccinia virus in a human host by analyzing the combined sets of virus targets and human genes that are required for viral infection. We also considered targets and required genes of bacteriophages lambda and T7 infection in Escherichia coli. We found that targeted proteins and their immediate network neighbors significantly pool with proteins required for infection and essential for cell growth, forming large connected components in both the human and E. coli protein interaction networks. The impact of both viruses and phages on their protein targets appears to extend to their network neighbors, as these are enriched with topologically central proteins that have a significant disruptive topological effect and connect different protein complexes. Moreover, viral and phage targets and network neighbors are enriched with transcription factors, methylases, and acetylases in human viruses, while such interactions are much less prominent in bacteriophages. IMPORTANCE While host-virus interaction interfaces have been previously investigated, relatively little is known about the indirect interactions of pathogen and host proteins required for viral infection and host cell function. Therefore, we investigated the topological relationships of human and bacterial viruses and how they interact with their hosts. We focused on those host proteins that are directly targeted by viruses, those that are required for infection, and those that are essential for both human and bacterial cells (here, E. coli). Generally, we observed that targeted, required, and essential proteins in both hosts interact in a highly intertwined fashion. While there exist highly similar topological patterns, we found that human viruses target transcription factors through methylases and acetylases, proteins that played no such role in bacteriophages.